Characterization of Seeding Conditions for Studies on Differentiation Patterns of Subventricular Zone Derived Neurospheres - Sanchez-Mendoza, Eduardo H.; Schlechter, Jana; Hermann, Dirk M.; Doeppner, Thorsten R. (Frontiers in Cellular Neuroscience, 2016)
Stem cell research depends on extensive in vitro research. Poly-D-Lysine (PDL) and Polyornithine (PornT) are chemically synthesized amino acid chains promoting cell adhesion to solid substrates. Although PDL and PornT are extensively used, there is no common agreement regarding the most optimal substance and its concentration. We therefore aimed at testing the effect of increasing concentrations (10, 50 and 100 µg/ml) for each compound and their corresponding mixtures (5+5 and 10+10 µg/ml) on the differentiation patterns of subventricular zone derived neurospheres. The latter were cultured for 24 h for protein and morphological analysis or for 8h for migration analysis. No significant differences were found between increasing concentrations of PDL and PornT alone and the 10+10 condition in Western blots and immunocytochemistry. However, the mixed condition of 5+5 showed decreased GFAP and nestin expression with no changes in Akt, pAkt, GSK-3-beta and pGSK-3-beta expression patterns. The various coating conditions also had no influence on migration of cells emerging from the neurosphere. Nevertheless, stimulation with recombinant human Erythropoietin (rhEpo) reduced migration by 20% regardless of the coating condition. We therefore conclude that a minimal concentration of 10 µg/ml of either compound should be used to produce reliable results with no alterations in protein levels as found for the 5+5 group, and that the coating has no effect on the response of cells to chemical interventions. As such, a concentration of 10 µg/ml for either substance is sufficient when studying cellular processes of neurospheres in an in vitro or ex vivo environment.